1999
DOI: 10.1523/jneurosci.19-01-00503.1999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Receptor Subtype Involved in the Analgesic Effect of Neurotensin

Abstract: The neuropeptide neurotensin (NT) elicits hypothermic and naloxone-insensitive analgesic responses after brain injection. Recent pharmacological evidence obtained with NT agonists and antagonists suggests that these effects are mediated by a receptor distinct from the initially cloned high-affinity NT receptor (NTR1). The recent cloning of a second NT receptor (NTR2) prompted us to evaluate its role in NT-induced analgesia. Intracerebroventricular injections in mice of two different antisense oligodeoxynucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
105
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 33 publications
7
105
0
1
Order By: Relevance
“…This compound, first identified as a NTS1 antagonist, presented a higher affinity for this receptor than for NTS2, while the analog SR 142948A did not discriminate between these two 5 receptors [25]. Experiments performed with these compounds [25,37,71] as well as intracerebral injection of anti-receptor antisense oligonucleotides [19] or evaluation of knockout mice [59], suggested that most of the NT effects could be attributed to stimulation of NTS1. However, the functional importance of NTS2 and NTS3 might still be largely underestimated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound, first identified as a NTS1 antagonist, presented a higher affinity for this receptor than for NTS2, while the analog SR 142948A did not discriminate between these two 5 receptors [25]. Experiments performed with these compounds [25,37,71] as well as intracerebral injection of anti-receptor antisense oligonucleotides [19] or evaluation of knockout mice [59], suggested that most of the NT effects could be attributed to stimulation of NTS1. However, the functional importance of NTS2 and NTS3 might still be largely underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…However, the functional importance of NTS2 and NTS3 might still be largely underestimated. Several arguments suggest that NTS2 mediates analgesic effects of NT [19,44,81]. Recent data otherwise revealed a role of NTS3 in mediating NT effects on microglial migration, cytokine/chemokine expression and proliferation of cancer cell lines [17,18,47].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, knockdown strategies, using either NTS2 antisense oligonucleotides (Dubuc et al, 1999) or NTS2-deficient mice, markedly inhibit NT-induced antinociception (Maeno et al, 2004). The presence of high levels of NTS2 mRNA and of strong NTS2 immunolabeling in regions implicated in pain regulation (such as the periaqueductal gray, nuclei raphe dorsalis, magnus, pallidus, and gigantocellularis, pars alpha) was also interpreted as circumstantial evidence for a role of NTS2 receptors in antinociception (Sarret et al, 1998Walker et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was to take advantage of recently developed antibodies against rat NTS2 and stable NT analogs displaying preferential affinity for NTS2 (LabbeJullie et al, 1994;Dubuc et al, 1999) to investigate the distribution of NTS2 in spinal cord and DRGs and its implication in spinal analgesia. Indeed, whereas neurons expressing NTS1 mRNA had been reported in DRG neurons (Zhang et al, 1995) and high concentrations of NTS1 binding sites, and NTS1-immunoreactive nerve cell bodies and fibers had been detected in the substantia gelatinosa of the dorsal horn (Ninkovic et al, 1981;Kar and Quirion, 1995;Fassio et al, 2000), nothing was known about the distribution of NTS2 receptors in these two areas.…”
Section: Introductionmentioning
confidence: 99%
“…Using an NTR1-knockout mice model, it has been found that NTR1 is involved in the control of food consumption and body weight, but not in NT-induced analgesia (Remaury et al 2002). On the other hand, NTR2 seems to account for the SR 48692-insensitive analgesic effect (Dubuc et al 1999, Maeno et al 2004. Recent studies have shown that NTR3 may control proliferation of human cancer cells (Dal Farra et al 2001), migration of human microglia (Martin et al 2003) and proNGF-induced neuronal cell death (Nykjaer et al 2004).…”
Section: Introductionmentioning
confidence: 99%